2021
DOI: 10.1101/2021.09.20.461118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidized thioredoxin-1 restrains the NLRP1 inflammasome

Abstract: At least six human proteins detect danger-associated signals, assemble into complexes called inflammasomes, and trigger pyroptotic cell death. NLRP1 was the first protein discovered to form an inflammasome, but the danger signals and molecular mechanisms that control its activation have not yet been fully established. Here, we report that the NACHT-LRR region of NLRP1 directly binds to oxidized form of thioredoxin-1 (TRX1). We found that NLRP1 requires the ATPase activity of its NACHT domain to associate wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…MeBs, which synergizes with VbP to induce more pyroptosis in these cell lines, was used as a positive control in this experiment (Chui et al, 2019; Orth-He et al, 2022). Consistent with our previous results (Ball et al, 2021), we found that dithiothreitol (DTT), N-acetyl cysteine (NAC), reduced L-glutathione (GSH), and trolox did not impact VbP-induced NLRP1 or CARD8 activation ( Fig. 1A,B , Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…MeBs, which synergizes with VbP to induce more pyroptosis in these cell lines, was used as a positive control in this experiment (Chui et al, 2019; Orth-He et al, 2022). Consistent with our previous results (Ball et al, 2021), we found that dithiothreitol (DTT), N-acetyl cysteine (NAC), reduced L-glutathione (GSH), and trolox did not impact VbP-induced NLRP1 or CARD8 activation ( Fig. 1A,B , Fig.…”
Section: Resultssupporting
confidence: 92%
“…CRISPR/Cas9 gene editing. DPP8/9, CARD8, and CASP1 knockout THP-1 cell lines and all HEK293T, RAW 264.7, N/TERT-1, and MV4;11 knockout cell lines were generated as previously described (Ball et al, 2021;Johnson et al, 2018;Okondo et al, 2017;Sharif et al, 2021). Briefly, 5´ 10 5 HEK 293T cells stably expressing Cas9 were seeded in 6-well tissue culture dishes in 2 mL of media per well.…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations